2015
DOI: 10.1364/ol.40.004257
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive waves induced by self-defocusing temporal solitons in a beta-barium-borate crystal

Abstract: We experimentally observe long-wavelength dispersive waves generation in a BBO crystal. A soliton was formed in normal GVD regime of the crystal by a self-defocusing and negative nonlinearity through phase-mismatched quatradic interaction. Strong temporal pulse compression confirmed the formation of soliton during the pulse propagation inside the crystal. Significant dispersive wave radiation was measured in the anomalous GVD regime of the BBO crystal. With the pump wavelengths from 1.24 to 1.4 µm, tunable dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…This type of dispersive wave is quite similar to the one observed in Kerr media, since it is mediated by fourwave mixing (FWM, degenerate 28,32 or non-degenerate case 28,33 ), but with the cascaded quadratic nonlinearity we also found that there is a unique three-wave mixing (TWM) analogue. This was recently observed experimentally for the first time 34 , where we found that in BBO the SH beam had a parametrically tunable peak, i.e.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…This type of dispersive wave is quite similar to the one observed in Kerr media, since it is mediated by fourwave mixing (FWM, degenerate 28,32 or non-degenerate case 28,33 ), but with the cascaded quadratic nonlinearity we also found that there is a unique three-wave mixing (TWM) analogue. This was recently observed experimentally for the first time 34 , where we found that in BBO the SH beam had a parametrically tunable peak, i.e.…”
Section: Introductionsupporting
confidence: 72%
“…to the long-wavelength side 30,31 . This was recently experimentally verified in bulk BBO and LN 28,32 , and together with the soliton the dispersive wave(s) constitute the octavespanning supercontinuum in the self-defocusing soliton case, which for LN can extend from 1.0-4.0 µm.…”
Section: Introductionmentioning
confidence: 64%
“…More recent numerical and experimental results show that the long wave side of the SC radiation could be enriched by the generation of broadband dispersive waves located beyond the zero dispersion wavelength of the crystals: together with the soliton the dispersive waves contribute to the octave spanning SC, which extends from 1.0 to 4.0 μm in LN [238] and from 0.9 to 2.3 μm in β-BBO [239] crystals. More recently, this approach was extended to the nonlinear crystals that are transparent in the mid-infrared range [240].…”
Section: Birefringent Crystalsmentioning
confidence: 99%
“…Recently other non-standard 4WM terms were shown to support RR waves, namely the conjugate SPM term |A| 2 A * [13-16] and third-harmonic generation term A 3 [17, 18].Phase-mismatched (cascaded) three-wave mixing (3WM) in quadratic nonlinear crystals can generate a negative self-defocusing Kerr-like nonlinearity [19,20], and when a temporal soliton is excited [21] this gives octave-spanning supercontinua [22][23][24][25] that are filament free [26][27][28][29]. So far, only RR waves generated by the cascaded self-defocusing SPM effect have been verified [27][28][29]. In this Letter we show that a new class of RR waves exist in quadratic nonlinear crystals, induced by the soliton through the 3WM processes sum-frequency generation (SFG, A 2 ) and difference-frequency generation (DFG, A * A).…”
mentioning
confidence: 99%